Relationships among Perceived Stress, Spousal Support, Emotion Regulation, Subjective Well-Being, and Marital Satisfaction of Thai First-Time Parents - Watcharakitippong, Juntita; Blauw, Jon; Tuicomepee, Arunya (Scholar: Human Sciences, 2018)
Parenthood is new to first-time parents. While it brings excitement, hope, and joy, being a parent for the first time also brings stress and challenges as a result of the new roles and responsibilities that ‘first-timers’ have to confront during the early years of being parents. The current investigation attempted to examine the direct and indirect influences of perceived stress and spousal support on marital satisfaction, being mediated by emotion regulation strategies (cognitive reappraisal, expressive suppression) and subjective well-being (positive affect, negative affect, life satisfaction) among Thai first-time parents. In Study I and II, a total of 559 first-time parents with one child (or twin) aged no more than two years-old and living in Bangkok and suburbs participated. They were asked to complete a set of survey questionnaires in Thai, consisting of a demographic section, the Perceived Stress Scale, the Multidimensional Scale of Perceived Social Support-Significant Others subscale, the Emotion Regulation Questionnaire, the Positive and Negative Affect Schedule, the Satisfaction with Life Scale, and the Couples Satisfaction Index. The results revealed that the ‘direct’ path model is significantly better fitting and more parsimonious than the indirect or full path models, and that the structural path relationships of the ‘full’ path model between the variables operated differently for first-time fathers and mothers. Additionally, emotion regulation played different roles between fathers and mothers.